ENHANCING MULTILINGUAL DIGITAL MARKETING COMPETENCE THROUGH ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY AT THE MAGELANG CITY VOCATIONAL TRAINING CENTER (UPT BLK) - Purnamasari, Dwi Candra; Wijaya, Ayudhia Ratna; Januaristi, Khairiyah Eka; Agwinanda, Almira (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service project focuses on enhancing multilingual digital marketing competencies through the utilization of artificial intelligence (AI) technology at the Job Training Center (UPT Balai Latihan Kerja) of Magelang City. The program was designed to improve the skills of MSME (Micro, Small, and Medium Enterprises) participants in leveraging AI for digital marketing, with an emphasis on the effective creation of multilingual content. The project was implemented in three main stages: (1) Planning, which involved preparatory activities, identification of participants' needs, and the development of relevant training materials; (2) Implementation, as the core phase, in which participants received hands-on training on the application of AI technologies particularly ChatGPT for generating marketing content, social media posts, and blog articles in multiple languages; and (3) Evaluation, during which participants' competency improvements were measured through direct assessments of their generated content and the completion of questionnaires. The evaluation results indicated a significant improvement in participants' abilities to produce engaging and multilingual digital marketing content, as well as a deeper understanding of AI utilization in marketing strategies. This program is expected to make a substantial contribution to expanding the market reach of MSMEs and enhancing their competitiveness in an increasingly global market environment.